Bioactive compounds from Apama Corymbosa / Siti Zaiton Mat So'ad and Nik Idris Yusoff - Mat So'ad, Siti Zaiton; Yusoff, Nik Idris (Universiti Teknologi MARA Cawangan Pahang, 2002)
Apama corymbosa (Grifl)Willd. (Syn. Thottea corymbosa Griff) known as akar julong bukit, akar surai (Malay) is a shrub found in the forests of Malaysia and Sumatra. Preliminary studies on Apama tomentosa showed that the plant contained Aristolochic acid, Aristololactam, steroid and fatty acids. Aristolochic acid has been reported to increase phagocytosis of leucocytes and exhibit tumour inhibitory activity. The roots of T.corymbosa collected from Ayer Hitam Forest Reserve, Puchong were extracted by conventional method using petroleum ether,chloroform and methanol. In this paper we will discuss the isolation and purification of the toxic crude from chloroform extract. Brine Shrimp Lethallity Bioassay gave LCso-200 ppm. Separation and isolation of the components were carried out using chromatographic methods(CC,PTLC,FCC,SPE). Structural identifications were achieved by spectroscopic methods i.e. GC-MS,IR,UV, 'H- and 13C-NMR. As a result three major known compounds isolated were identified as Ariskanin-A, Ariskanin-D and Cepharadione-A.